Accuracy of the Maxwell–Wagner and the Bruggeman–Hanai mixture models for single cell dielectric spectroscopy. Issue 7 (26th July 2017) - Mansoorifar, Amin; Ghosh, Arindam; Sabuncu, Ahmet C.; Beskok, Ali
Abstract : Dielectric spectroscopy (DS) is a non‐invasive, label‐free, and promising technique for measuring dielectric properties of biological cells. Recent developments in microfabrication techniques made it possible to perform DS measurements with minute volume of cell suspensions. However, when the cell size approaches the size of the measurement chamber, especially, for single cell measurements, the analytical models [Maxwell–Wagner and Bruggeman–Hanai (BH) mixture models] to extract cell parameters lose their accuracy. Moreover, variations in the cell position relative to the measurement electrodes decrease the accuracy of the analytical solutions. Impedance spectrum of a typical eukaryotic mammalian cell is generated for different geometrical configurations using finite element. The generated data are fitted to the analytical models and extracted cell parameters are compared with the original values. The results show that BH model works more effectively when chamber to cell radius ratio is <3.5 and chamber height to cell radius ratio is <3. Moreover, it is observed that analytical models estimate cell parameters with major errors when the cells are in the vicinity of the electrodes. However, for high‐volume fraction simulations, the BH model was able to predict cell parameters better even in the vicinity of the electrodes.